Tap Settings Optimization in Power Systems: Economic Efficiency Enhancement Through Cuckoo Search Algorithm While Ensuring Voltage Stability - Raizal N.I.; Mansor M.H.; Musirin I.; Shaaya S.A.; Ismail S.A.; Ismail N.L. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper presents an approach to enhance the economic efficiency of power systems through tap settings optimization using Cuckoo Search Algorithm (CSA), while ensuring voltage stability. With the escalating demand for electrical power, power system networks face challenges such as voltage decay, increased current flows, and energy losses. Reactive power planning, including tap settings optimization, plays a crucial role in addressing these challenges and optimizing system performance. Specifically, this study focuses on the role of on-load tap-changing transformers (OLTCs) in regulating voltage levels without interrupting the power supply. CSA is employed as an optimization technique due to its effectiveness in handling complex and nonlinear optimization problems. The objectives of the optimization process include minimizing active power losses and generation costs while maintaining voltage stability. The IEEE 26-Bus Reliability Test System (RTS) is used as a test system to demonstrate the implementation and effectiveness of the proposed approach. It has been found that CSA successfully improved the power system operation in terms of reduced active losses and generation costs compared to the non-optimal solution obtained from the power flow analysis. The results contribute to enhancing the economic efficiency of power systems and provide valuable findings for power system planning and operation. 2023 IEEE.